Exploring gender dynamics in ski jumping : women’s perspectives on gender roles and (in)equality - Ikonen, Anastasia (2024)
Even though Finland has made progress in matters of gender equality, gender inequalities still exist, especially in sport. This master’s thesis delves into gender equality, particularly in the context of ski jumping organizations. Ski jumping has long been a male-dominated field of business, where women's participation has been low. This work provides an overview of the development of women's participation in ski jumping, identifying gender inequalities associated with socially constructed gender roles and their effect on women's position, development and career progression in ski jumping activities. Theoretical framework of this study comprises theories on gender norms as social structures that reinforce power dynamics and create inequalities in sport organizations, such as gender discrimination, limited opportunities, division of labor, and wage gaps between genders. To find out if gender roles exist and how they affect women's socioeconomic status in ski jumping, qualitative research methods are used. For this study, five women engaged in ski jumping have been interviewed, whose experiences of the prevalence of gender roles and their influence on gender equality in the field have been analyzed using the hermeneutic phenomenological method. The research findings reveal that gender roles remain deeply ingrained in ski jumping culture. Prevailing gender roles hinder women’s participation in all sport-related activities within the ski jumping context. Gender stereotyping contributes to unequal resource allocation and task distribution, affecting women’s career development as athletes, coaches, experts, officials, and leaders. Moreover, the results identify how low gender diversity and high male dominance in ski jumping organizations influence decision-making processes hindering individuals’ and organizational performance. Based on the research findings, ski jumping organizations are provided with practical recommendations and encouraged to implement proactive measures to address gender equality issues and foster positive change in organizational culture.